Pendampingan Satuan Pendidikan Untuk Percepatan Implementasi Kurikulum Merdeka (IKM) Bagi Guru Dan Kepala Sekolah PAUD, SD, SMP Se-Kecamatan Padang Jaya Korwil IV Bengkulu Utara - Martiani Martiani; Mariska Febrianti; Azizatul Banat (Jurnal Dehasen Untuk Negeri, 2023)
Kurikulum Merdeka is a learning program that suits students' abilities, and provides a wider space for character development and basic competencies. The independent curriculum is a new curriculum that is implemented to schools with project-based learning. With the implementation of the new curriculum, teachers, principals and students must adapt to the renewal. This activity aims to help overcome teachers' problems in implementing Kurikulum Merdeka to schools in North Bengkulu Regency, especially in the understanding aspect of P5 and also the implementation of Platformn Merdeka Mengajar. This activity is carried out as a form of community service by using socialization and training methods, personal approaches and peer tutors. The results obtained from this community service activity can be interpreted that the activity participants consisting of school principals and teachers in North Bengkulu Regency of Regional Coordinator IV can understand material regarding P5 and the features available on platform Merdeka Mengajar. In addition, for advanced programs, it is necessary to hold similar activities with material regarding the results of using platform Merdeka Mengajar so that Principals and Teachers in North Bengkulu Regency can be motivated and enthusiastic to learn and fill in PMM to accelerate the implementation of Kurikulum Merdeka.